Agronomic performance of common bean lines and cultivars in the Cerrado/Pantanal ecotone region (Research, Society and Development, 2020)
Beans have been widely cultivated throughout Brazil. However, low productivity indexes have been obtained with the cultivation of many cultivars available on the market, so the use of genetic improvement can be a technology to develop more productive bean cultivars adapted to the specific conditions of each Brazilian region. The objective of this study was to evaluate the agronomic characteristics and reaction to diseases in 19 common bean genotypes of the Carioca trade group, among strains and commercial varieties, to obtain information about genotypes with better productive potential in the aquidauana region, MS. The experiment was conducted during the "dry" harvest. The experimental design adopted was in randomized blocks, with three replicates and 19 treatments (cultivars Pérola and BRS Estilo and the lines BRS CNFC 10429, BRS CNFC 10762, CNFC 15003, CNFC 15010, CNFC 15018, CNFC 15023, CNFC 15025, CNFC 15033, CNFC 15035, CNFC 15038, CNFC 15049, CNFC 15070, CNFC 15082, CNFC 15086, CNFC 15097, CNFC 15001, CNFC 15044). The genotypes were evaluated for the following traits: Days for flowering (DFL); Days for physiological maturation (MFD); Plant height (APL); Number of pods per plant (NVP); Number of grains per pod (NGV); Mass of 100 grains (MCG); Grain yield (PROD) and Disease incidence. The genotypes Pérola, BRS CNFC 10429, CNFC 15086, CNFC 15082 were more productive and adapted to the Cerrado-Pantanal ecotono region of Mato Grosso do Sul, and all are susceptible to bacterial cresting.